E-Governance - Perri, P. author. aut Link
XII, 238 p.
Keywords: The e-governance revolution is said to be changing everything, but will all the modelling tools, electronic meeting management systems and online consultations really change political judgement in policy formation? Using case studies from local and federal government in the US and Europe, Perri 6 examines these claims and presents a new theory of how policymakers use and reject information and do and don't trust each other with information in using the new tools, before analyzing the implications for democracy.